Fostering learning among the next generation of veterinarians: incorporating one health and antimicrobial stewardship into veterinary medicine training curricula in Ethiopia - Nyokabi, N.; Phelan, L.; Berg, S.; Lindahl, Johanna F.; Korir, L.; Bett, Bernard K.; Muunda, Emmanuel; Mihret, A.; Moore, H.; Wood, J. (Frontiers Media, 2026)
Universities play a crucial role in educating and training veterinarians, and their fostering of learning among the next generation of students is widely regarded as key to bringing about the cultural change required to realise a transition towards a ‘One Health’ approach to managing human, animal, and environmental health and underpin widespread adoption of antimicrobial stewardship practices. In Africa, there is a paucity of studies that have explored how veterinary training curricula are influencing veterinary medicine students’ perceptions of ‘One Health’ and the importance of antimicrobial stewardship. This study takes Ethiopia as a case study and explores how veterinary medicine students’ training influences perceptions regarding the benefits of taking a ‘One Health’ approach to managing public health risks and adhering to rational antimicrobial prescription practices and drug use. Data for this study were collected through an online questionnaire survey administered to 154 veterinary students at universities across Ethiopia. We found that the veterinary students were interested in receiving training related to the ‘One Health’ concept and indicated that such training would increase the likelihood that, upon graduation, they would be competent practitioners who could collaborate with other health sectors practitioners in addressing public health challenges. The students perceived a gap in the veterinary training curricula regarding rational antimicrobial prescribing and drug use; this is a concern given that antimicrobial resistance is an emerging problem in Ethiopia and worldwide. The results of this study underscore that veterinary training curricula play a key role in shaping students’ mindsets and practice, and that the provision of information, interdisciplinary and transdisciplinary practical training, and mentorship is key to fostering the learning required to ensure that students are holistic practitioners with the knowledge and capacity to implement at ‘One Health’ approach and antimicrobial stewardship in the future careers. The results highlight the imperative and opportunity for higher education institutions, particularly universities, and policymakers to ensure that national veterinary curricula are cognisant of and aligned with emerging approaches—such as the One Health approach, which advocates for interdisciplinary and multidisciplinary collaboration and communication - to managing the risks posed by infectious diseases to public health.